Before appeasement : Stresa Conference and the failure of the common security in Europe as reported by the Manchester Guardian and Neuer Vorwärts in 1935 - Vesala, Esa (2021)
The research of my thesis has been focused on the 1935 diplomatic conference at Stresa, in Northern Italy and observe how this meeting between the representatives of the United Kingdom, France and Italy shaped the diplomatic relations in interwar Europe. The goal of this meeting was to formulate a common policy against Germany in reaction to the founding of the German air force. This action, which reneged on the 1919 treaty of Versailles caused great worry in Europe. The aim of my research has been to examine developments that rose from this and examine what measures the tripartite powers adopted in opposition to the German aims of territorial expansion and confrontation with the neighbouring powers, mainly Lithuania and Poland in these early stages. The paramount view presented in the context of these developments is, that in 1935 the Tripartite powers of the United Kingdom, France and Italy were much more willing to concretely challenge German aggression than after 1935 when the policy of appeasement replaced this willingness to both challenge and curtail German influence in concord with different associated powers. As a method of research, I have examined multiple newspaper sources on the matter through qualitative analysis and further built my argument on the previously conducted research. As a method of research, I have employed methods of discourse analysis with the theory of social agency of the reporters in this. In addition, my choice of sources, The Manchester Guardian and the exiled German social-democratic newspaper, Neuer Vorwärts are chosen as the main sources in this. In lieu of these sources, reflected with the previous research on the matter, I present an argument. In light of the research I have conducted, the tripartite powers and their attempts to maintain a policy of common action against Germany were one of the most concrete ways in which German expansionism was challenged before the world war and that it was its failure that gave way to appeasement. I have presented the developments as they occurred, reflecting the early hopes of the success of the pact towards the foundational disagreements that had begun to tear the pact apart mere months after its formation. Accompanying this are presented the last attempts by the British and the French governments to reform this anti-German pact. From my research, it can be seen that the slide to appeasement was not sudden or found some unwillingness to challenge German plans for hegemony in Europe. Instead, the appeasement is presented as arising from the failure of the tripartite powers to uphold their policy of collaboration against Germany. From my thesis, it can be interpreted that interwar Europe was not simply following the rise of the Nazi regime with bated breath, but actively sought to contain and even challenge the spread of Nazi influence in the European continent. Shift to appeasement is also present in the form of the Anglo-German naval agreement, in which Germany's right to rearm was officially recognised by one of the tripartite powers, the United Kingdom.